OP0191 Disease-Associated SNPS from Non-Coding Regions in Juvenile Idiopathic Arthritis Are Located within or Adjacent to Functional Genomic Elements of Human Neutrophils. (10th June 2014) - Jiang, K.; Liu, T.; Buck, M.J.; Chen, Y.; Carrier, B.; Jarvis, J.
Abstract : Background: The completion of a largegenome-wide associate study (GWAS) for juvenile idiopathic arthritis (JIA) revealed multiple regions conferring disease risk [1]. However, the majority of disease-associated SNPs occurred in non-coding regions of the genome. Objectives: To identify functional elements that might be associated with disease-associated SNPs in polyarticular, RF-negative JIA. Methods: We generated a genome wide map of histone marks associated with enhancer elements in adult neutrophils. Using chromatin immunoprecipitation/sequencing (ChIPseq) approaches, we mapped the histone marks associated with poised (H3K4me1+/H3K27ac-) or active (H3K4me1+/H3K27ac+) enhancers to the GRCh37/hg19 genome assembly. We also performed paired-end RNA sequencing on neutrophils from 5 children with untreated polyarticular, RF-negative JIA and mapped reads to the same genome assembly. Results were used to interrogate ENCODE and Roadmap Epigenomics data using the UCSC Genome browser to interrogate the 22 polyarticular JIA associated SNPs from non-coding regions genome identified by Hicks et al. Results: There are functional elements in neutrophil genomes in or adjacent to 13 of the 22 SNP regions identified by Hicks et al. Enhancer elements were the most frequently identified functional elements in this study, with 9 potentially active (H3K4me1+/H3K27ac+) and 3 additional potentially poised enhancers identified. We also identified 4 non-coding transcripts within the SNP regions. Four of these regions (e.g., both of the SNPs around C5orf56-IRF1) contained both non-coding RNA transcripts and enhancer elements. It was also interesting to note abundant intronic transcription in other genes relevant to inflammation/immunity but not otherwise known to confer genetic risk e.g., CD36. Conclusions: Regions of genetic risk for polyarticular JIA are rich with functional elements that regulate and coordinate transcription in human neutrophils. These data provide a new framework from which to understand genetic risk and disease pathogenesis in JIA, and suggest that transcriptional regulation and coordination may be a process that is fundamentally perturbed in this disease. References: Hinks A, Cobb J, Marion MC, Prahalad S, Sudman M, Bowes JG, Martin P, Comeau ME, Sajuthi S, Andrews R, Brown M, Chen WM, Concannon P, Deloukas P, Edkins S, Eyre S, Gaffney PM, Guthery SL, Guthridge JM, Hunt SE, James JA, Keddache M, Moser KL, Nigrovic PA, Onengut-Gumuscu S, Onslow ML, Rosé CD, Rich SS, Steel KJA, Wakeland EK, Wallace CA, Wedderburn LR, Woo P, Boston Children's JIA Registry, British Society of Paediatric and Adolescent Rheumatology (BSPAR) Study Group, Childhood Arthritis Prospective Study (CAPS), Childhood Arthritis Response to Medication Study (CHARMS), German Society for Pediatric Rheumatology (GKJR), JIA Gene Expression Study, NIAMS JIA Genetic Registry, TREAT Study, United Kingdom Juvenile Idiopathic Arthritis Genetics Consortium (UKJIAGC), Bohnsack JF, Haas PJ, Glass DN, Langefeld CD, Thomson W, Thompson SD, Dense genotyping of immune-related disease regions identifies 14 new susceptibility loci for juvenile idiopathic arthritis. Nature Genet 2013; 45: 644-669. Acknowledgements: This work was supported by AR-R01-060604 from the National Institutes of Health and an Innovative Research from the Arthritis Foundation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4577